2010
DOI: 10.1155/2010/428673
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Spermatogenesis and Nucleolar Behavior in Testicular Lobes ofEuschistus heros(Heteroptera: Pentatomidae)

Abstract: In some testicular lobes of the Pentatomidae there may be occurrence of atypical spermatogenesis or polymegaly, leading to the production of nonfertile sperm. The comparative analysis of spermatogenesis and nucleolar behavior in testicular lobes of Euschistus heros showed cells with polymegaly in lobes 4 and 6. Generally, when these lobes are present in the same individual, there is also the formation of atypical cells in the flanking lobe. Such characteristic was not seen in E. heros. However, differences reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In all the examined individuals, the fifth lobe was thinner than the others, and had spermatic cells larger in diameter than those of the first to third lobes but smaller than those of the fourth and sixth lobes, as reported by Souza and Itoyama (). The presence of spermatozoa with different sizes and diameters was corroborated in E. heros : Cossolin () described three types of sperms different in the morphology and ultrastructure.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In all the examined individuals, the fifth lobe was thinner than the others, and had spermatic cells larger in diameter than those of the first to third lobes but smaller than those of the fourth and sixth lobes, as reported by Souza and Itoyama (). The presence of spermatozoa with different sizes and diameters was corroborated in E. heros : Cossolin () described three types of sperms different in the morphology and ultrastructure.…”
Section: Discussionsupporting
confidence: 82%
“…The present study revealed that the testicules were essentially identical in morphology among individuals from the three experimental sources of E. heros , being approximately 2 mm in length and having six lobes as observed in specimens collected in the State of São Paulo by Souza and Itoyama (). The number of lobes varies from three to eight, with the prevalence of seven, among species of the family Pentatomidae (Souza & Itoyama ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to the literature, the number of lobes in the family Lygaeidae is variable, with species with two, four, six and seven lobes, where seven is considered the ancestral number (Grozeva & Kuznetsova, 1992). According to the literature, Limnogonus aduncus (Gerridae, Castanhole et al, 2008) (Souza & Itoyama, 2010) includes six species of the subfamily Asopinae, in which only one species (Euthyrhynchus floridanus) has six testicular lobes and the others seven. In the other subfamilies, the distribution of lobes differs, ranging from four to eight in the Discocephalinae, four to five in the Edessinae and three to seven in the Pentatominae.…”
Section: Discussionmentioning
confidence: 99%
“…In the Discocephalinae, for example, the harlequin is usually lobe 5, numbered from the ejaculatory duct. In most cases, when lobes 4 and 6 show polymegaly, lobe 5 shows atypical meiosis, with the only exception being Euschistus heros (Pentatomidae: Carpocorini), which in addition to lacking a harlequin lobe, has a very narrow fifth lobe (Souza & Itoyama, 2010). The present study found that Proxys albopunctulatus (Pentatomidae: Carpocorini) belongs this select group, i.e., it lacks a harlequin lobe, and lobe 5 is flanked by lobes that produce differentiated cells and has a small diameter.…”
Section: Discussionmentioning
confidence: 99%